Proces Przejściowy w Hydraulicznym Układzie Nieliniowym - Bednarz, S.; Kasprzyk, S. (Engineering Transactions, 1964)
This paper contains an analysis of the transition process of a servo as described by the differential equationx ̈+a_1 x ̇+b_1 x- c_1 √(d_1-x ̇ )=0,where a1, b1, c1, d1 are constants.The dependency of the transitory process on the parameters of the system are determined by means of a topologic method in the phase plane. Equations are obtained interrelating the parameters in the case where the system is stable and the conditions to be satisfied if no oscillation is to take place.